Feeding Practices and Nutritional Status of Infants and Young Children Aged 6-23 Months in the South Kivu Region: A Cross-Sectional Study - Nabuholo, Marie Amélie; Mama, Olouwafemi Mistourath; Diouf, Adama; Bahizire, Esto; Idohou-Dossou, Nicole (International Journal of Child Health and Nutrition, 2025)
Background: The increasing prevalence of stunting in the Democratic Republic of the Congo (DRC) represents a major public health concern. Adequate complementary feeding is crucial for preventing and reducing chronic malnutrition in early childhood in the long term. Objective: This study aimed to assess the baseline complementary feeding practices and nutritional status of children aged 6–23 months in South Kivu Province, with a focus on commonly consumed complementary foods. Methods: A cross-sectional analytical study was conducted among 515 children in the Kadutu and Miti-Murhesa health zones of South Kivu. Participants were selected through a systematic random sampling method. Dietary intakes and infant feeding practices were assessed using dietary recall questionnaires and a 7-day food frequency questionnaire. The nutritional status was measured by anthropometry. Results: The mean age of children was 13.3 ± 5 months. Results showed that 59% of the children had a low dietary diversity score. Only 23% received an appropriate complementary feeding according to the minimum acceptable diet. Most of the children (88.5%) consumed porridge made exclusively of cereals, roots, or tubers and water. Animal-source foods, fruits, and vegetables were rarely consumed. Acute malnutrition and stunting affected 4.9% and 36.6% of children, respectively. Conclusion: Stunting remains prevalent in both rural and urban areas of South Kivu. Furthermore, infant diets are nutritionally inadequate, as evidenced by their lack of diversity. Enriching widely consumed staple foods (maize, sorghum, and soy) with locally available animal-source products could improve micronutrient intake and constitute a promising strategy for preventing child malnutrition.